Proof-of-Concept Randomized Controlled Study of Cognition Effects of the Proprietary Extract Sceletium tortuosum (Zembrin) Targeting Phosphodiesterase-4 in Cognitively Healthy Subjects: Implications for Alzheimer's Dementia. (23rd October 2014) - Chiu, Simon; Gericke, Nigel; Farina-Woodbury, Michel; Badmaev, Vladimir; Raheb, Hana; Terpstra, Kristen; Antongiorgi, Joalex; Bureau, Yves; Cernovsky, Zack; Hou, Jirui; Sanchez, Veronica; Williams, Marissa; et al.
Abstract : Introduction . Converging evidence suggests that PDE-4 (phosphodiesterase subtype 4) plays a crucial role in regulating cognition via the PDE-4-cAMP cascade signaling involving phosphorylated cAMP response element binding protein (CREB). Objective . The primary endpoint was to examine the neurocognitive effects of extract Sceletium tortuosum (Zembrin) and to assess the safety and tolerability of Zembrin in cognitively healthy control subjects. Method . We chose the randomized double-blind placebo-controlled cross-over design in our study. We randomized normal healthy subjects (total n = 2 1 ) to receive either 25 mg capsule Zembrin or placebo capsule once daily for 3 weeks, in a randomized placebo-controlled 3-week cross-over design. We administered battery of neuropsychological tests: CNS Vital Signs and Hamilton depression rating scale (HAM-D) at baseline and regular intervals and monitored side effects with treatment emergent adverse events scale. Results . 21 subjects (mean age: 54.6 years ± 6.0 yrs; male/female ratio: 9/12) entered the study. Zembrin at 25 mg daily dosage significantly improved cognitive set flexibility (P < 0 . 0 3 2 ) and executive function (P < 0 . 0 2 2 ), compared with the placebo group. Positive changes in mood and sleep were found. Zembrin was well tolerated. Conclusion . The promising cognitive enhancing effects of Zembrin likely implicate the PDE-4-cAMP-CREB cascade, a novel drug target in the potential treatment of early Alzheimer's dementia. This trial is registered with ClinicalTrials.gov NCT01805518 .